2021
DOI: 10.1007/s42452-020-04043-9
|View full text |Cite
|
Sign up to set email alerts
|

Empirical models for estimating the global solar radiation of Jubail Industrial City, the Kingdom of Saudi Arabia

Abstract: Empirical models provide precise and cost-effective information on solar energy assessment. The main objective of this work is to create and examine some regression models (linear, quadratic and logarithmic), for the estimation of the monthly global solar radiation potential in the Jubail Industrial City of Saudi Arabia. The industrial city has more solar energy potential, and the global horizontal irradiance is ranging from 4000 to 7000 Wh/m2/day. In order to initiate the green energy development in the city,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The Kingdom of Saudi Arabia is located in the world's sun-belt at 36.6-50 • E longitudes and 17.5-31 • N latitudes with an annual average solar radiation of 2200 kWh/m 2 [100]. Hot water demand is an important part of energy consumption in the residential sector of this country, where electric water heaters consume the majority of the energy, especially in the wintertime.…”
Section: Saudi Arabiamentioning
confidence: 99%
“…The Kingdom of Saudi Arabia is located in the world's sun-belt at 36.6-50 • E longitudes and 17.5-31 • N latitudes with an annual average solar radiation of 2200 kWh/m 2 [100]. Hot water demand is an important part of energy consumption in the residential sector of this country, where electric water heaters consume the majority of the energy, especially in the wintertime.…”
Section: Saudi Arabiamentioning
confidence: 99%
“…They developed three regression models comprising relative humidity and temperature as inputs variables and GHI as an output variable. In another similar work, three regression models were proposed for global solar radiation prediction [22], in which three features, namely ambient temperature, relative humidity, and sunshine hours, were taken as independent variables. It is observed that, compared to the linear model, the quadratic model provides better prediction accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most traditional models incorporating maximum and minimum temperatures are the Hargreaves and Samani and Bristow and Campbell models [4,10]. Both models are the basis of innovative approaches adapted to specific location conditions [7,12,27,[29][30][31][32].…”
Section: Empirical Temperature-based Modelsmentioning
confidence: 99%